2017
DOI: 10.1002/adhm.201700127
|View full text |Cite
|
Sign up to set email alerts
|

tBHQ Suppresses Osteoclastic Resorption in Xenogeneic‐Treated Dentin Matrix‐Based Scaffolds

Abstract: Extracellularmatrix (ECM)-based scaffolds are important for their potential therapeutic application. Treated dentin matrix (TDM), a kind of ECM, seeded with allogeneic dental follicle stem cells (TDM/aDFC) provides a suitable inductive microenvironment for tooth root regeneration. Considering the limited sources, xenogeneic TDM (xTDM) is a possible alternative to allogeneic TDM; however, xTDM-based scaffold presents severe osteolysis and resorption lacunae causing regenerated tooth root failure. Immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…TDM is a bioactive scaffold that derives from native dentin and retains the porous structure and functional proteins. Numerous studies have documented TDM potential for tooth root or dentin reconstruction/regeneration (Chen et al, ; Chen et al, ; Guo et al, ; Ji et al, ; Jiao et al, ; Li et al, ; Li, Sun, et al, ; Luo et al, ; Luo et al, ; Sun et al, ; Yang et al, ). Previously, studies found that TDM released several dentinogenesis‐related factors such as biglycan, collagen‐1, decorin, DMP‐1, DSP, and TGF‐β1 (Jiao et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TDM is a bioactive scaffold that derives from native dentin and retains the porous structure and functional proteins. Numerous studies have documented TDM potential for tooth root or dentin reconstruction/regeneration (Chen et al, ; Chen et al, ; Guo et al, ; Ji et al, ; Jiao et al, ; Li et al, ; Li, Sun, et al, ; Luo et al, ; Luo et al, ; Sun et al, ; Yang et al, ). Previously, studies found that TDM released several dentinogenesis‐related factors such as biglycan, collagen‐1, decorin, DMP‐1, DSP, and TGF‐β1 (Jiao et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…ECM‐based biomaterials can be produced from almost any tissue in the body, such as the bladder (Dahms, Piechota, Dahiya, Lue, & Tanagho, ), blood vessels (Dahl, Koh, Prabhakar, & Niklason, ), bone (Frohlich et al, ), dermis (Reing et al, ), heart valves (Rieder et al, ), kidney (Nakayama, Batchelder, Lee, & Tarantal, ), ligaments (Woods & Gratzer, ), liver (Uygun et al, ), nerves (Hudson et al, ), skeletal muscle (Conconi et al, ), small intestinal submucosa (Badylak et al, ), and tendons (Ning et al, ). Furthermore, our previous studies described the use of treated dentin matrix (TDM), a natural ECM‐based scaffold, for tooth root regeneration (Guo et al, ; Li et al, ; Sun et al, ; Yang et al, ). By a gradient ethylene diamine tetra‐acetic acid (EDTA) demineralization treatment, dentin tubules were exposed and allows releasement of odontogenic factors, which makes TDM a bioactive scaffold (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the scant sources of allogeneic TDM (aTDM), xenogeneic TDM (xTDM) was a possible substitute for aTDM but it caused osteolysis and resorption lacunae and led to regenerated root failure. The tert -butylhydroquinone ( t BHQ), an antioxidant, can reduce osteolysis and osteoclastic resorption when added in xTDM/aDFCs scaffolds [154].…”
Section: Clinical Application Potential Of Dfcsmentioning
confidence: 99%
“…Dental follicle stem cells (DFSCs), as clonogenic cells, also have the ability of multilineage differentiation and could differentiate into cementoblasts, neural-like cells, membrane-like structures and periodontal ligament(PDL)like tissue [11][12][13][14]. And a novel method for biological tooth root regeneration was reported, which apply tertbutylhydroquinone (tBHQ) treatment of scaffolds, derived from treated dentin matrix (TDM) that is seeded with allogeneic dental follicle stem cells (TDM/aDFC) to prevent osteoclastic resorption and produce a tooth root [15]. So DFSCs seem to be a promising choice to restore a tooth root.…”
Section: 2dental Follicle Stem Cells (Dfscs)mentioning
confidence: 99%